Governance with complex structures: evidence from Western European countries - Santos, Mário S.; Moreira, António C.; Vieira, Elisabete S. (Journal of Business Economics and Management, 2014)
This paper investigates if the existence of complex structures plays an important role in corporate governance. It uses GMM estimation on a panel of Western European firms. We find that the presence of a second and third large shareholder has a significant positive effect on firm value. This study underlines the importance of the number of blockholders as a determinant of firm value, when taken as a moderator of the contestability effect. It shows that the legal context and company-specific characteristics play a crucial moderating role for contestability. In contrast to previous research, we find that contestability plays a less relevant role in family firms. We also find that this last result does not vary significantly with the identity of the remaining elements of the coalition. Also, our study suggests that contestability is less important in companies led by majority shareholders.